2017
DOI: 10.18632/oncotarget.16418
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluoride PET/CT tumor burden quantification predicts survival in breast cancer

Abstract: PurposeIn bone-metastatic breast cancer patients, there are no current imaging biomarkers to identify which patients have worst prognosis. The purpose of our study was to investigate if skeletal tumor burden determined by 18F-Fluoride PET/CT correlates with clinical outcomes and may help define prognosis throughout the course of the disease.ResultsBone metastases were present in 49 patients. On multivariable analysis, skeletal tumor burden was significantly and independently associated with overall survival (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
3
12
0
1
Order By: Relevance
“…The starkest differences occurred among lung cancer patients. Our findings that positive NaF PET assessed qualitatively is associated with lower survival rates are consistent with other published reports that have focused on the association between tumor burden assessed quantitatively by NaF PET and survival (20)(21)(22)(23)(24). We could find no similar research on admission to hospice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The starkest differences occurred among lung cancer patients. Our findings that positive NaF PET assessed qualitatively is associated with lower survival rates are consistent with other published reports that have focused on the association between tumor burden assessed quantitatively by NaF PET and survival (20)(21)(22)(23)(24). We could find no similar research on admission to hospice.…”
Section: Discussionsupporting
confidence: 90%
“…Only a few small, single-center studies have evaluated the association between NaF PET results and cancer survival (20)(21)(22)(23)(24). The relative survivals reported in these studies were similar to those reported here, except for 2 studies (22,24) that reported differences of lesser magnitude, based on NaF PET results, than we found.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that a baseline 18 F-fluoride PET/CT study plays a prognostic role in patients with breast or prostate cancer treated with 223 RaCl 2 ( 1 , 14 ) . However, 18 F-fluoride PET/CT is not traditionally used in evaluating the response to any therapy, because the process of bone healing involves an osteoblastic reaction than can increase 18 F-fluoride uptake, as in conventional bone scintigraphy ( 15 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Semiautomatic quantification of wholebody skeletal tumor burden with 18 F-fluoride PET/CT (TLF 10 and FTV 10 ) has been shown to be a strong and independent prognostic biomarker in breast (6) and prostate (7,14) cancers. To the best of our knowledge, semiautomatic quantification of 18 Ffluoride PET/CT had not previously been validated for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the determination of 18 F-fluoride PET/CT whole-body skeletal tumor burden is able to objectively assess response to treatment and is a better prognostic indicator than visual analysis (4,5). Investigators have demonstrated a prognostic role for 18 F-fluoride PET/CT in breast (6) and prostate (7) cancers. Therefore, quantitative parameters with 18 F-fluoride PET/CT can be important for clinical evaluation of patient outcome and for clinical trials, by eliminating subjectivity and assessing response to therapy.…”
mentioning
confidence: 99%